Characterization of four new monoclonal antibodies against the distal N-terminal region of PrPc - Didonna,Alessandro; Venturini,Anja Colja; Hartman,Katrina; Vranac,Tanja; Curin Serbec,Vladka; Legname,Giuseppe (PeerJ PrePrints, 2014)
Prion diseases are a group of fatal neurodegenerative disorders that affect humans and animals. They are characterized by the accumulation in the central nervous system of a pathological form of the host-encoded prion protein (PrPC). The prion protein is a membrane glycoprotein that consists of two domains: a globular, structured C-terminus and an unstructured N-terminus. The N-terminal part of the protein is involved in different functions in both health and disease. In the present work we discuss the production and biochemical characterization of a panel of four monoclonal antibodies (mAbs) against the distal N-terminus of PrPC using a well-established methodology based on the immunization of Prnp0/0 mice. Additionally, we show their ability to block prion (PrPSc) replication at nanomolar concentrations in a cell culture model of prion infection. These mAbs represent a promising tool for prion diagnostics and for studying the physiological role of the N-terminal domain of PrPC.
Keywords: Prion protein; Monoclonal antibodies; Immunohistochemistry; Prion inhibition